The More Similar, the Healthier: The Effect of Perceived Parent-Child Facial Resemblance on Parental Physical Health - Yu, Quanlei; Guo, Yafei; Zhang, Lin; Chen, Jianwen; Du, Xiaopeng; Wei, Xinhui; Zhou, Zhijin; Liu, Shumin; Gao, Xinlei (Frontiers in Psychology, 2019)
Parent-child facial resemblance (PCFR) is one of the most distinguished features to roughly assess the genetic relation between two individuals. Due to the inner fertilization of humans, fathers are liable to suffer from the risk of paternal uncertainty. When a father perceives low father-child facial resemblance, he would fall into lasting anxiety, which were detrimental to the immune system and physical health. For a mother, however, she can assure her genetic relation to children and do not need any external cues to verify the maternity. Thus, the mother-child facial resemblance could not influence mothers’ physical health. We recruited 110 parents from 110 independent families to examine the moderating effect of parent gender and mediating effect of trait anxiety on the relationship between PCFR and parental physical health. The results showed that parent gender moderated the relationship between PCFR and parental health. Only fathers’ PCFR positively predicted their physical health. Besides, trait anxiety mediated the relationship between fathers’ PCFR and their physical health. The implications for paternal uncertainty, gender difference research and public policy were discussed.